Gambaran Anti-Plasmodium sp. Pada Anggota Tentara Nasional Indonesia Angkatan Darat Di Kota Cimahi - Patricia Gita Naully; Gina Khairinisa; Dewi Ratih Saputri (Universitas Muhammadiyah Surabaya, 2018)
Malaria is a disease caused by Plasmodium sp. The presence of such parasites in body can be characterized by the presence of anti-Plasmodium sp. antibodies. Malaria cases are still prevalent in Indonesia and generally occur in people who travel to endemic areas. One of the jobs that obliges its members to serve to various regions, including endemic areas is the Indonesian Army (TNI AD). Many Army personnel residing in Cimahi City. The purpose of this study is to determine the overview of malaria in members of the Army in Cimahi City. This study used a sample of 30 TNI AD who are residing in Cimahi City and have been assigned to various regions in Indonesia. Venipucture is only performed on respondents who have signed informed consent and filled out the interview form. Malaria screening is performed using immunochromatography that can detect anti-P. vivax and anti-P. falciparum antibodies, with a high degree of sensitivity and specificity. Of the 30 people, there were 4 people (13.3%) who had been infected with malaria and 2 (6.7%) of whom had experienced mixed malaria. All respondents who tested positive for malaria claimed to have been assigned to malaria endemic areas such as Papua and Maluku for several years.